MODUS OPERANDI KORUPSI DAN KAITANNYA DENGAN APARATUR NEGARA DALAM HADIS-HADIS NABI DAN PERUNDANG-UNDANGAN DI INDONESIA - H. Rajab (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
The Modus Operandi of Corruption and its Relation to the State Apparatus in the Prophet's Hadiths and Legislation in IndonesiaThis paper aims to explain the modes of corruption and their relation to the state apparatus in the Prophet's traditions and legislation in Indonesia. So far, when many people talk about corruption, their memory is only of the laws that govern it, as if only the laws and regulations regulate corruption. In fact, long before the legislation was made, the Prophet, through his hadiths, have provided clues about corruption. This research is qualitative descriptive using a literature study that relies on library sources in the form of classic books, books, scientific journals, and other literature sources that are considered relevant. This study finds similarities between the Prophet's hadiths and Indonesian legislation in linking corruption (al-gulūl) to the state apparatus ('āmil) and that the modes of corruption are budget fraud, abuse of authority, embezzlement, and gratification and bribe. The mode then increases and develops with the times. Hopefully, through this writing, there will be awareness again that involvement in corruption is not only a violation of laws but also a violation of religious teachings and its legal consequences not only in the world but also in the hereafter.